Pharmacological approaches to the treatment of tinnitus - Elgoyhen, Ana Belen (2010)
Tinnitus is the conscious perception of a phantom sound in the absence of an external source. For 1 in 100 of the general population, the condition severely affects quality of life. In spite of the fact that the market for a drug indicated for tinnitus relief is huge, there are still no FDA-approved drugs, and the quest for a tinnitus-targeted compound faces important challenges. A wide variety of drugs have been used off-label to treat tinnitus sufferers, with limited but significant effects in subsets of patients. If the compounds being developed at present by the pharmaceutical industry finally reach the market, they will establish a turning point in the treatment of this pathology.